2010
DOI: 10.1007/s11999-010-1411-8
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Risk Factors for Infection in Hemiarthroplasties and Total Hip Arthroplasties?

Abstract: Background Late infection is the second most frequent early complication after total hip arthroplasty (THA) and the most frequent after hemiarthroplasty. Known risk factors for infection after THA include posttraumatic osteoarthritis, previous surgery, chronic liver disease, corticoid therapy, and excessive surgical time. However, risk factors for hemiarthroplasty are not clearly established. Questions/purposes We therefore determined the preoperative and intraoperative risk factors for late infection (more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
2
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(118 citation statements)
references
References 35 publications
1
103
2
8
Order By: Relevance
“…After 1 year of followup, no patient in either group presented signs of arthroplasty infection (Table 3). Cordero-Ampuero and de Dios [6] reported urinary infection is a risk factor for deep prosthetic infection in hemiarthroplasties. Urinary catheterization, especially if longterm or repeated, is more frequent in PJIs in patients undergoing HA [7].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…After 1 year of followup, no patient in either group presented signs of arthroplasty infection (Table 3). Cordero-Ampuero and de Dios [6] reported urinary infection is a risk factor for deep prosthetic infection in hemiarthroplasties. Urinary catheterization, especially if longterm or repeated, is more frequent in PJIs in patients undergoing HA [7].…”
Section: Discussionmentioning
confidence: 97%
“…Urinary infection is a reported risk factor for hematogenous PJI [2,3,6,12,16,22,25,27,28,32]. A related but absolutely different clinical situation, asymptomatic bacteriuria, presents an increasing prevalence with age and female sex, from 1% among schoolgirls to [ 40% among women older than 80 years [4,11,14,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is currently a limited amount of data that describes the postoperative complications of THA associated specifically with chronic corticosteroid use. Some studies have found that patients who take corticosteroids chronically are at increased risk for readmission [16], implant failure [15] and postoperative infection [5,13,22] after THA. However, other studies found no increases in the likelihood of readmissions for complications, including periprosthetic joint infection [2] and implant failure [4], after THA in this population.…”
Section: Introductionmentioning
confidence: 99%